(untitled) (Bulletin KNOB, 2007)
It is strange that in the Netherlands towns and villages can be protected, but old landscapes can’t. Although the legislator did offer this possibility in the Nature Conservation Act of 1998, it has not been taken advantage of so far. Nevertheless, this ought to happen on penalty of losing the last remnants that have been preserved of the cultural-historical landscape. Why haven’t any landscapes been protected vet? This is probably due to a widespread repugnance to actions originating in nostalgic feelings among the general public. Moreover, another factor here is that ecological nature conservation is blind to the role played or possibly to be played by farming in the conservation of the cultural-historical landscape. Still a major part of the cultural-historical landscape consists of farmland. Because of the rapidly changing economy of agriculture, it is now time to ask the question to what extent the old farmland should be left to the free-market process in this sector. Is a form of protection by means of subsidised farms worth considering? The latter is strongly discouraged by various experts in government service. The author of the present article, however, does plead for it and compares this form of protection with the protection of historical towns and villages.